Digitizing the Monolingual Lusoga Dictionary: Challenges and Prospects - Nabirye, Minah; de Schryver, Gilles-Maurice (Lexikos, 2013)
This article recounts the genesis, growth and turbulent events that accompanied the compilation of the Eiwanika ly’Olusoga, that is, the Monolingual Lusoga Dictionary. Contrasting academia with the trade, legacy with state-of the-art dictionary compilation software, high praise and visibility with daily and down-to-earth drudgery, it recounts the events chronologically, from humble to grand, from paper to digital, from success to insignificance, and leads to a set of highly realistic proposals to be considered by all those involved in the compilation of explanatory dictionaries for the African languages.